Dynamika rozwoju społeczno-gospodarczego grup ludzkich w starożytności i we wczesnym średniowieczu na tle środowiska naturalnego w mikroregionie tucholskim - Kmieciński, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 1990)
The elaboration of the oldesthistory of human groups within the range of microregion faces significant difficulties especially in case of the very little amount of written sources. The author discusses the development of the settlement in the area of Tuchola Forests considering archaeological sources and taking into account the results of related sciences such as biology or sciences of the Earth. On the grounds of them he concludes that territorial organization developed in the northern part of Tuchola Forests is in agreement with the development of the whole area of Gdańsk Pomerania.